EFEKTIFITAS TEKNIK RATIONAL EMOTIF BEHAVIOR THERAPY (REBT) KONSELING KELOMPOK UNTUK MENGURANGI KECEMASAN MENGHADAPI UJIAN TAHFIDZ DI PONDOK PESANTREN IBNU KATSIR 2 JEMBER - Khoiriyatun Hasanah; Nasruliyah Hikmatul Maghfiroh; Wahid Suharmawan (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2024)
The objective of this study is to analyze the efficacy of the Rational Emotive Behavior Therapy (REBT) approach in diminishing students' anxiety levels while preparing for the tahfidz test at the Ibnu Katsir 2 Jember Islamic Boarding School. This study follows a group pre-test post-test design. The sample for this research included 31 students, of whom 10 individuals reported severe levels of anxiousness. A questionnaire was used as the data gathering method in this investigation. The research findings indicate that the anxiety level associated with the tahfidz test reduced after treatment with the REBT approach. This is evident from the findings of the pretest and posttest study, in the pretest the score shows a high leve of anxiety and the posttest shows the score of the low level of anxiety, so it can be concluded that the level of anxiety in facing the tahfidz exam has decreased in score. So it can be concluded that the REBT technique is effective in reducing anxiety in facing the tahfidz exam at the Ibnu Katsir 2 Jember Islamic Boarding School.